Parasocial Relationships as a Mediator of YouTube Vlog Credibility and Gen Z Travel Intentions - Ananda Nurul Fauziyah; Ratih Hasanah Sudradjat (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study examined the influence of message credibility in educational travel vlogs on Generation Z’s travel intention, with parasocial relationships as a mediating variable. Using a quantitative descriptive approach and SEM-PLS analysis, data were collected from 400 active viewers of the YouTube channel @leonardoedwin. The results showed that message credibility had a significant effect on travel intention (β = 0.783) and parasocial relationships (β = 0.186). Parasocial relationships also significantly influenced travel intention (β = 0.512) and partially mediated the effect of message credibility (β = 0.401). These findings supported the Two-Step Flow Communication Theory, where content creators act as opinion leaders who influence audience behavior through emotional connection. The study concluded that a combination of informational credibility and parasocial engagement played a crucial role in shaping persuasive communication, particularly in fostering travel intention among Gen Z audiences in the digital era.